1983
DOI: 10.1111/j.1365-3024.1983.tb00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Site of expression of immunity to Naegleria fowled in immunized mice

Abstract: An experiment was performed which confirmed a previous finding that mice are protected against Naegleria fowleri infection by immunization with amoeba-free supernatant from amoeba cultures. Histological observations suggested that this protection is expressed mainly at the nasal mucosa and possibly results from the combined effects of polymorphonuclear leucocyte-mediated killing of the amoeba and mechanical elimination of the organisms by extensive shedding of necrotic epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Several reports (Ferrante and Mocatta 1984;Ferrante 1989) have shown that neutrophils fail to kill the ameba in vitro unless they are exposed to inflammatory cytokines (TNF-a). In addition, in vivo studies have proposed that activation of neutrophils is important in the defense against infection by N. fowleri in mice (Thong et al 1983;Ferrante et al 1988Ferrante et al , 1989. Moreover, neutrophils do not seem to have amebicidal activity in spite of the close association of large numbers of neutrophils with amebas.…”
Section: Discussionmentioning
confidence: 96%
“…Several reports (Ferrante and Mocatta 1984;Ferrante 1989) have shown that neutrophils fail to kill the ameba in vitro unless they are exposed to inflammatory cytokines (TNF-a). In addition, in vivo studies have proposed that activation of neutrophils is important in the defense against infection by N. fowleri in mice (Thong et al 1983;Ferrante et al 1988Ferrante et al , 1989. Moreover, neutrophils do not seem to have amebicidal activity in spite of the close association of large numbers of neutrophils with amebas.…”
Section: Discussionmentioning
confidence: 96%
“…This fact has discouraged the development of a vaccine strategy directed at stimulating humoral immunity against this parasite. However, Thong et al, (28), based on their antibody transference results, showing partial protection to Naegleria infection, suggested that this strategy may provide a lead to the development of immunotherapy for this virulent disease, for which satisfactory chemotherapy is presently unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that one of the main defence mechanisms of the nasal mucosa against N. fowleri in mice is the phagocytosis of trophozoites by polymorphonuclear cells (32). Although the Fcα/RI and Fcα/µR receptors for the Fc fraction of the IgA have not been described for murine neutrophils (28), the fact that of neutrophils adhere to amoebas covered with IgA suggests that these polymorphonuclears may interact with the IgA on the surface of trophozoites through other yet undefined receptors for the Fc fraction of IgA or for the secretory component (33).…”
Section: Discussionmentioning
confidence: 99%